Manipulation of Rest Period Length Induces Different Causes of Fatigue in Vertical Jumping - Pereira, G. [UNESP]; Morse, C.; Ugrinowitsch, C.; Rodacki, A.; Kokubun, Eduardo [UNESP]; Fowler, N. (Georg Thieme Verlag Kg, 2009)
The aim of this study was to directly compare the causes of fatigue after a short- and a long-rest interval between consecutive stretch-shortening cycle exercises. Eleven healthy males jumped with different resting period lengths (short = 6.1 +/- 1 s, long = 8.6 +/- 0.9 s), performing countermovement jumps at 95% of their maximal jump height until they were unable to sustain the target height. After short- and long-rest, the maximal voluntary isometric contraction knee extension torque decreased (-7%; p = 0.04), comparing to values obtained before exercise protocols. No change was seen from pre- to post-exercise, for either short- or long-rest, in biceps femoris coactivation (-1%; p = 0.95), peak-to-peak amplitude (1%; p = 0.95) and duration (-8%; p = 0.92) of the compound muscle action potential of the vastus lateralis. Evoked peak twitch torque reduced after both exercise protocols (short = -26%, long = -32%; p = 0.003) indicating peripheral fatigue. However, central fatigue occurred only after short-rest evidenced by a reduction in voluntary activation of the quadriceps muscle (-14%; p = 0.013) measured using the interpolated twitch technique. In conclusion, after Stretch-shortening cycle exercise using short rest period length, the cause of fatigue was central and peripheral, while after using long rest period length, the cause of fatigue was peripheral.
Keywords: stretch-shortening cycle; neuromuscular parameters; intermittent exercise; twitch interpolation; M-wave